The Influence of Transformational Leadership Style, Organizational Commitment on Employee Productivity - Hidayah, Lailatul; Alfany, Andri (AGILITY: Jurnal Lentera Manajemen Sumber Daya Manusia, 2025)
This study aims to analyze the influence of transformational leadership style and organizational commitment on employee productivity at PT Katolec Indonesia. Transformational leadership styles, with dimensions of ideal influence, inspirational motivation, intellectual stimulation, and individual attention, have proven to be instrumental in driving employees to perform above expectations. Organizational commitment serves as a mediating variable that strengthens the relationship between transformational leadership and productivity. This study used a quantitative approach with a purposive sampling method, involving 69 respondents, and analyzed using SmartPLS. The results showed that organizational commitment had a significant influence on employee productivity (p<0.05), while the influence of transformational leadership style was moderate (p=0.06). The majority of respondents were young employees with secondary education backgrounds who worked in the production division. This study provides insight into the importance of synergy between transformational leadership styles and organizational commitment in creating an innovative and productive work environment. Practical recommendations include program policy development, employee empowerment, and increased strategic commitment through employee participation and equitable system improvements.